PRODUCTION OF ASPHALT. MODERN TECHNOLOGIES ININSTALLATIONS - Chanev, Ivan (E-Journal VFU, 2024)
In general, the main components of asphalt concrete installations, which are also main energy consumers, lead to the need to consider the implementation of photovoltaicinstallations in asphalt bases as a valuable tool for reducing costs, improving n and sustainability and minimization of the impact on the environment. While they come with certain challenges, the benefits of these facilities make investing in them a worthwhile consideration for asphalt base owners and operators
Keywords: technologies; production; asphalt concrete